Economic Analysis of Milk Phoduction on Range Lands in Exthemely Arid Districts of Western Rajasthan - Kalla, Jagdeesh C; Bhati, G N; Mertia, R S; Bawa, A K (Annals of Arid Zone, 2016)
The milch-productivity of Tharparkar and Rathi herds kept at Chandan (Jaisalmer district) and Beechwal (Bikaner district) range-lands in extreme arid conditions was evaluated by production function and project evaluation techniques. Despite variations in productivity performances due to breed and spatial factors. the herd size. quantity of fodder grazed and supply of concentrates turned out to be important determinants of milk production at both the locations. The results of measures of project evaluation revealed sound resilience and economic viability of milk production system on improved grasslands at the selected locations. The results conclusively established grassland development programme as a precondition to optimize milk production in arid areas.